Agricultural Soil as a Reservoir of Pseudomonas aeruginosa with Potential Risk to Public Health - Jessica I. Licea-Herrera; Abraham Guerrero; Maribel Mireles-Martínez; Yuridia Rodríguez-González; Guadalupe Aguilera-Arreola; Araceli Contreras-Rodríguez; Susana Fernandez-Davila; Rocío Requena-Castro; Gildardo Rivera; Virgilio Bocanegra-García; Ana Verónica Martínez-Vázquez (Microorganisms)
Pseudomonas aeruginosa is an opportunistic pathogen with a high capacity to adapt to different factors. The aim of this study is to analyze the pathogenicity in P. aeruginosa strains and their resistance to heavy metals and antibiotics, in agricultural soil of the state of Tamaulipas, Mexico. Susceptibility to 16 antibiotics was tested using the Kirby-Bauer method (CLSI). Eight virulence factors (FV) and six genes associated with heavy metal resistance were detected by PCR. As a result, P. aeruginosa was detected in 55% of the samples. The eight virulence factors were identified in ≥80% of the strains. The strains showed some level of resistance to only three antibiotics: 32.8% to ticarcillin, 40.8% to ticarcillin/clavulanic acid and 2.4% to aztreonam. The most frequent heavy metal resistance genes were arsC (92.8%) and copA (90.4%). However, copB and arsB genes were also identified in a percentage greater than 80%, and the least frequent genes were merA in 14.4% and czcA in 7.2%. Although P. aeruginosa strains showed a high percentage of factor virulence (potential ability to cause infections), their high levels of susceptibility to antibiotics lead to the assumption that infections are easily curable.